Post-earthquake response by small UAV helicopters - Nedjati, Arman; Vizvari, Bela; Izbirak, Gokhan (Springer, 2016)
The aim of this study was to introduce a new relief distribution system for emergency response after an earthquake. Extensive literature is used to explain the ground transportation difficulties following a disaster and some possible alternative choices. Due to roads blockage and time limits in the disaster response phase, small unmanned aerial vehicle (UAV) helicopter can be utilized as relief distributors. The use of UAV helicopters for humanitarian purposes and even for commercial purposes by some companies has been discussed in several publications. Yet no one has considered an autonomous small UAV helicopter network for post-earthquake relief distribution in highly populated cities. In an applied sense, the study offers a system that helps earthquake response managers in the early hours following an earthquake. The suggested system is a synthesis of many new technical results achieved in the area of earthquake detection, data fusion, and UAV helicopters. The relief distribution system by medium-scale UAV helicopters is investigated in Tehran metropolis as a case study for the worst-case earthquake scenario. The outcomes reveal that the system has efficient capability for urban areas with high population density. The proposed aerial distribution system can supply a large amount of demand in a small amount of time. Moreover, it works without disturbing the ground transportation system and may turn out to be managed as a complementary system for serving the affected people in non-accessible areas.
Keywords: Emergency response; Earthquake; UAV helicopter; Relief distribution; Disasters